ANÁLISE DO TEMPO DE INTERNAMENTO NA UTI DE PACIENTES ATENDIDOS EM UM HOSPITAL UNIVERSITÁRIO EM CURITIBA-PR - PETTERLE, Ricardo Rasmussen; OLIVEIRA NETTO, Ana Cristina Schmidt de; MIALSKI, Rafael; KRIEGER, Marco Aurelio; MORELLO, Luis Gustavo; COSTA, Libera Maria Dalla; RABONI, Sonia Mara (Brazilian Journal of Biometrics, 2018)
Sepsis, also known as septicemia, is a clinical disease that affects the immune system of the patient. This disease is among the main causes of mortality in ICUs, besides being responsible for high costs of treatment and long periods of hospitalization. In this context, the present study presents an application of the Gompertz regression model and the Cox regression model in the analysis of ICU stay in critical patients treated at a university hospital in Curitiba-PR, Brazil. The study evaluated three covariates: gender (male or female), ICU type (adult or pediatric) and sepsis (presence or absence). The results showed that gender was not an important characteristic in the study. However, patients with a diagnosis of sepsis and adult ICU were those who presented a higher risk of death.